Pembungkaman Terhadap Perempuan Dalam Teks Pemberitaan Syariat Islam (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2017)
Media has a big power to create public opinion about the position of gender. The asymmetry relation between man and woman always showed in the news coverage of media – as particulary in the Sharia news. Including to the Sharia News, woman became the figure which most frequently reported by the media. While the Sharia issues is abused by the media to naturalize the discrimination of woman. Many of Sharia cases in the reality was constructed by the media in such a way, which carried of dominant ideology that opressed the woman. At the last, the woman was muted by the media in Sharia news coverage